Interior Planning of the Flood Disaster Mitigation Education Center in Bekasi Regency - Nuraini, Fitria (Institut Seni Indonesia Surakarta, 2024)
The Interior Planning of the Flood Disaster Mitigation Education Center in Bekasi Regency aims to be a means of disaster risk reduction (mitigation) in the form of flood disaster education to the community in Bekasi. Activities including seminars, disaster exhibitions, video screenings, and flood disaster simulations according to guidelines of the Indonesian National Disaster Management Agency (BNPB). Design method uses the Kurtz Design Method which consists of orientation, the basic program, the programming repetition, and the design. The approaches of design use function, ergonomics, aesthetics, technical, and interior pandemic. Design results are interior planning of a flood disaster mitigation education center that accommodates safety and comfort in the design of facilities that adjust user activities, grouping-zoning, and relationships between spaces. These facilities are lobby, auditorium, exhibition room, film screening room, disaster simulation room, reading room, souvenir shop, and café. Safety and comfort aspects are applied to furniture, color selection, materials, lighting, acoustics, and security systems. The educational aspect is AR technology which makes it easier to deliver information of flood disaster to public, especially during the COVID-19. This plan applies the local theme of the Bekasi, namely